Effect of Body Positions on Lungs Volume in Asthmatic Patients : A Cross-sectional Study - Myint, Wai Wai; Htay, Mila Nu Nu; Htoo Htoo, Kyaw Soe; Low, Renjue; Gan, Shirying; Nur Syamimi, Yuan; Aaron Balanti, Mojini (SCIENCEDOMAIN international., 2017)
Aim: The purpose of our research was to investigate the effect of different body positions on lungs volume by conducting pulmonary function test (PFT) values of the asthmatic patients. The objectives were (1) to assess the correlation between pulmonary function and posture in adult patients with asthma, (2) to determine the best position with higher lungs volume that was preferable for the asthmatic patients to relieve the asthma attack and for rehabilitation approach. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted in the Reconstructive and Rehabilitative Center at University Malaysia Sarawak (UNIMAS) between December 2015 and June 2016. Methodology: The total of 30 participants was recruited in this study. Among them, 15 participants were asthmatic patients and 15 participants were non-asthmatic, control persons. All the participants were between 19-25 years of age and they were enrolled after they had signed a written consent. Participants were selected using the inclusion criteria and Spiro Excel PC based pulmonary function test (PFT Medicaid Systems) were administered. Spirometer measurements (FVC, FEV1) were taken in the standing, sitting and supine positions. Each measurement was taken two times and the average values were analyzed. The order of the body positions was randomized. Results: In the asthmatic group, the best position was supine with a mean±standard deviation (SD) of FEV1/FVC, 77.93±17.37. Whereas, in control group, the best position was standing with a mean±SD of FEV1/FVC, 90.12±5.97. The second best positions were sitting position in the asthmatic group (75.37±16.37) and supine position in control group (89.70±8.79). Finally, the standing position had the lowest lungs function in the asthmatic group (73.63±17.08) and sitting position in control group (88.53±11.17). Conclusion: Our study showed that supine was the best position for measuring FEV1 and FVC of asthmatic participants. Therefore, supportive positions such as supine or leaning to the wall are suggested to improve pulmonary function of the patients, especially during asthmatic attack.